Self-medication practice with anti-malarial drugs and its associated factors among patients with fever attending public health facilities in Dera District, Northwest Ethiopia - Wondimnew Desalegn Addis; Agmas Wassie Abate; Negede Yiheyis Tasew; Amare Yirga Abate; Belete Asnake Sitotaw; Abay Semagn Kassie; Elelta Mulugeta Ayalew; Birhanemaskal Malkamu; Kindie Mitiku (PLoS ONE, 2026)
Background The issue of self-medication with anti-malarial drugs is a critical public health challenge. Despite national guidelines promoting diagnostic-confirmed treatment, evidence addressing the prevalence of self-medication with anti-malarial drugs and drivers in Ethiopia is scarce. Therefore, this study aimed to bridge this gap and to provide meaningful insights into ongoing efforts to curb the misuse of anti-malarial drugs and helping the strategy of malaria eliminationby investigating the prevalence of self-medication with anti-malaria drugs and its associated factors. Methods An institution-based cross-sectional study was conducted in Dera District, Northwest Ethiopia, from June 1–30, 2025. A total of 591 febrile patients were selected using a stratified multistage sampling technique. Data were collected through interviewer-administered structured questionnaires developed by reviewing different related literatures. Data entry and analysis were done using Epi-Data version 4.6 and STATA 17. Multivariable binary logistic regression analysis was performed to identify factors associated with self-medication. Statistical significance was declared at a p-value less than 0.05. Result The prevalence of self-medication with anti-malarial drugs was 42.8% (95% CI: 38.9%–46.8%). Factors positively associated with self-medication included: monthly income of ≥5000 ETB (AOR = 1.64, 95% CI: 1.04–2.59), poor knowledge about malaria (AOR = 1.68, 95% CI: 1.12–2.55), poor risk perception towards self-medication (AOR = 2.10, 95% CI: 1.40–3.14), and distance ≤5 km from private drug sellers (AOR = 1.65, 95% CI: 1.10–2.47). Community-based health insurance membership was negatively associated with self-medication (AOR = 0.60, 95% CI: 0.41–0.88). Conclusion Self-medication with anti-malarial drugs was moderate (33.4%_66.6%) in the study area based on percentile classification. The findings highlighted the need for designing different strategies to reduce inappropriate drug use and promoting community-based health insurance enrollment.